Frequency-Tunable and Pattern Diversity Antennas for Cognitive Radio Applications - A. H. Ramadan; J. Costantine; Y. Tawk; C. G. Christodoulou; K. Y. Kabalan (International Journal of Antennas and Propagation)
Frequency-tunable microstrip antennas, for cognitive radio applications, are proposed herein. The approach is based on tuning the operating frequency of a bandpass filter that is incorporated into a wideband antenna. The integration of an open loop resonator- (OLR-) based adjustable bandpass filter into a wideband antenna to transform it into a tunable filter-antenna is presented. The same technique is employed to design a cognitive radio pattern diversity tunable filter-antenna. A good agreement between the simulated and measured results for the fabricated prototypes is obtained. The radiation characteristics of each designed tunable filter-antenna are included herein.